Pengaruh Gaya Hidup dan Harga terhadap Keputusan Pembelian Iphone Second di Kota Sampit - Lestari, Sely (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of lifestyle and price on purchasing decisions in the city of Sampit. The two control variables (K) are product quality and income. Data collection was carried out by distributing questionnaires to 60 respondents who used the second iPhone. Sampling was carried out using a non-probability sampling method, with a purposive sampling technique. Based on the results of data analysis, it shows that the questionnaire is valid and reliable. on the hypothesis test the result is that lifestyle has no effect on purchasing decisions and price has a significant positive effect on purchasing decisions.